The protagonist’s shadow and persona as the reflection of anti-hero in The Phantom of the Opera novel retold by Diane Namm - Ratih Dwi Raharto; Riana Permatasari (Universitas Islam Sultan Agung, 2019)
Personality of any character in a work of art has become significant to be analyzed since it contributes to the value of the story. This paper analyzes a work concerning the personality of the protagonist. Unlike most protagonists who have the role to perform the traditional traits of a hero, some protagonists on the other hand tend to depict the characteristics of a villain. Yet the protagonist is still the leading character who just fails to enact the virtue of the society. In this case, a study of the concept of anti-hero is applied in order to expose the characteristics of anti-hero through the findings of the personality of the protagonist. The object of the study is a novel by Gaston Leroux retold by Namm (2008) entitled The Phantom of the Opera which has profound sense of psychological issues related to the characters inside the story especially the protagonist. This paper exerts a descriptive qualitative method and applies the psychology approach. Using two archetypes by Carl Gustav Jung, this paper focuses on two contradictory archetypes which are the persona and the shadow. For further analysis using the concept of anti-hero, this paper will use both archetypes to identify the characteristics of anti-hero. Henceforth, this paper discovered about the portrayal of those archetypes along with the reflection of anti-hero characteristics performed by the protagonist. There are two findings, first, the portrayal of the phantom’s persona as the mysteriously creepy ghost to the society, Angel or Music to Christine and his shadow dealing with his crimes. Second, the characteristics of anti-hero used his persona and shadow to show that anti-hero is flouting the traditional hero virtue and gaining sympathy from reader even though his darker side is more dominant.